An integrative approach RAMS-LCC to support decision on design and maintenance of rail track - Giammaria Praticò, Filippo; Giunta, Marinella (International Conference “Environmental Engineering”, 2017)
In this paper a RAMS (Reliability, Availability, Maintainability, Safety) – LCCA (Life Cycle Cost Analysis) mixed approach is proposed in order to support decisions on design and maintenance strategies of rail tracks. RAMS management, usually applied in railway sector, lacks a life-cycle cost perspective and balance, while LCCA supports decisions on design options and maintenance strategies by means of an economic analysis in which costs and performance are assessed. Therefore, a Decision Support System, based on Life-Cycle Costing (LCC) analysis, should be developed, balancing short and long-term costs with performance (RAMS target). The model proposed accounts for a comprehensive life cycle cost analysis based not only on agency (e.g., construction, inspection, maintenance and renewal), and user costs (e.g., delay-related, etc.), but also on environmental costs (e.g., related to CO2e emissions). For RAMS analysis, a new method to measure the RAMS components and to define an overall indicator is proposed. Results show that the RAMS of a slab track is generally higher than the one of a ballasted track. In terms of present value of two solutions, the breakeven point between them is very far from the end of construction and this may impact public opinion and overall judgment.
Keywords: LCCA; RAMS; Railway track